(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
As one of the leading and fatal public health problems, skin cancer’s progression is highly influenced by chronic inflammatory reactions and oxidative stress, accompanied by DNA mutation. Need for multi-option, plant-based alternatives, as first mentioned by Michael Sporn in 1976, offering chemoprevention to prevent initiation or inhibit tumor promotion and progression, and/or chemoprotection by use of plant-derived immunostimulants with the intention of immune system stimulation to either slow down or stop cancer evolution has been established as acceptable standard treatment is costly and has severe side effects. The present study was designed to assess the chemopreventive effect of Celastrus paniculatus seeds against DMBA–induced skin carcinogenesis in Swiss albino mice followed by croton oil administration. Parameters assessed included tumor incidence, yield, size, average latent period, hematological subsets, oxidative stress markers (LPO, CAT), inflammatory cytokines (TNF-α, IL-6), and histopathology. The disease control group (DMBA + croton oil application) showed 100% tumor incidence, high tumor yield, large papillomas (>8 mm), elevated LPO, reduced CAT, increased TNF-α, and IL-6 levels. The treatment groups showed promising results in contrast to the respective control groups. The oral + topical 400 mg/kg group showed the most pronounced protection, with tumor incidence reduced to 13.4%, tumor yield 0.33/mouse, the smallest papillomas (<2 mm), near-normal skin in histological assessments, restored CAT, reduced LPO levels, and normalized systemic inflammatory marker levels. C. paniculatus methanolic seed extract demonstrated dose- and route-dependent chemopreventive effects, with oral + topical 400 mg/kg showing the most promising effects, suggesting potential as well as a safer alternative adjuvant therapy along with the standard care in skin cancer prevention.